2002
DOI: 10.2134/jeq2002.7360
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Abiotic–Biotic Mineralization of 2,4,6‐Trinitrotoluene (TNT)

Abstract: Munitions wastes such as TNT are widespread contaminants in soils and ground waters. We investigated a coupled abiotic-biotic treatment scheme for remediation of aqueous solutions of TNT. Mineralization of aqueous TNT (0.22 mM) was initially optimized with minimum reactant use (Fe3+ and H2O2) in light-assisted and dark, modified Fenton reactions at acidic and neutral pH. Complete TNT degradation occurred under all reaction conditions within 24 h. Using the optimum reactant concentrations, coupled abiotic-bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Combined degradation procedures have already been described in the literature Hess and Schrader 2002;Hwang et al 2000a, b;Kearney et al 1983;Schrader and Hess 2004), which, however, in contrast to our procedure all start with a photochemical treatment followed by a microbiological transformation. From a comparison of those results with the data presented here, the concept of a biological reduction of TNT prior to an oxidative photochemical treatment by advanced oxidation procedures (AOP) seems to be the most appropriate approach towards mineralization of TNT.…”
Section: Discussionmentioning
confidence: 96%
“…Combined degradation procedures have already been described in the literature Hess and Schrader 2002;Hwang et al 2000a, b;Kearney et al 1983;Schrader and Hess 2004), which, however, in contrast to our procedure all start with a photochemical treatment followed by a microbiological transformation. From a comparison of those results with the data presented here, the concept of a biological reduction of TNT prior to an oxidative photochemical treatment by advanced oxidation procedures (AOP) seems to be the most appropriate approach towards mineralization of TNT.…”
Section: Discussionmentioning
confidence: 96%
“…However, integrated chemical-biological treatment of industrial effluents is generally found to derive both economic and technical advantages over chemical oxidation alone (Scott and Ollis, 1995). Studies have already been conducted successfully coupling biologicalC chemical oxidation for the treatment of originally refractory industrial pollutants in wastewater (Gulyas et al, 1995;Stockinger et al, 1995;Jochimsen et al, 1997;Benitez et al, 2001;Akmehmet Balcioglu and Arslan, 2001;Arslan-Alaton and Akmehmet Balcioglu, 2002;Hess and Schrader, 2002). To our knowledge, the integrated chemicalCbiological treatment of real antibiotic formulation wastewater has not been reported so far.…”
Section: Biological Treatment Of Raw Ozonated and Perozonated Penicimentioning
confidence: 99%
“…Research on advanced oxidation processes (AOPs) used to promote degradation of trinitrotoluene (TNT) and other nitroaromatic compounds, in soil or aqueous solutions, has included Fenton reactions [1][2][3] and, in aqueous solution, has used TiO 2 -mediated photocatalytic reactions. [4][5][6] In these studies, the authors reported that OH• was the active mechanism of destruction due to its nature as a nonspecific oxidant that reacted with many organic compounds at near diffusion controlled rates.…”
Section: Introductionmentioning
confidence: 99%